Hemostasis in pregnant, parturient and puerperal women with preeclampsia - M. G. Mustafin; E. Yu. Yupatov; T. E. Kurmanbaev; R. M. Nibiullina; Yu. L. Timoshkova; A. A. Shmidt; N. V. Yakovlev (IRBIS LLC, 2020)
Introduction. Preeclampsia (PE) is a specific complication of pregnancy holding a lead place in maternal and perinatal morbidity and mortality worldwide. The development of PE in the maternal body is accompanied by severe hypercoagulation, disturbed anticoagulation and fibrinolytic systems. As a result, vascular microthrombosis in diverse organs with developing endothelial dysfunction, impaired utero-placental blood circulation emerge that leads to adverse perinatal outcomes.Aim: to study status of coagulation arm in pregnant women with moderate and severe PE, after delivery by cesarean section, to optimize management of the postoperative period.Materials and Methods. There were enrolled 50 pregnant women with PE: 16 with moderate and 34 with severe PE after surgical delivery. A status of coagulation arm was examined by evaluating major parameters in coagulogram (fibrinogen, activated partial thromboplastin time, prothrombin, international normalized ratio) as well as assay for early diagnostics of blood clotting disorders to reveal bleeding and thrombosis risks.Results. It was found that prior to surgery patients with severe PE had significantly increased clot growth rate (V) by 1.09-fold (p = 0.001), relative clot density (D) by 1.15-fold (p = 0.001), and time of spontaneous clot appearance (Tsp) was accelerated by 2-fold (p = 0.001) compared to moderate PE. After surgical delivery, patients from both groups had changes evidencing about activated coagulation system: increased V, D, as well as the Tsp. Upon that, all such parameters in patients with severe PE were significantly elevated: the V - by 1.25-fold (p = 0.005); the D - by 1.1-fold (p = 0.02); the Tsp was accelerated by 2-fold (p = 0.03) compared to patients with moderate PE. All parameters in both groups tended to normalize on day 5 after surgical delivery, but patients with severe PE were shown to have significantly increased the V - by 1.5-fold (p = 0.001); the D - by 1.14-fold (p = 0.001); the clot size - by 1.14-fold (p = 0.001); the Tsp - accelerated by 41 % (p = 0.001) compared to patients with moderate PE.Conclusion. Thus, patients with moderate and severe PE after surgical delivery by cesarean section were featured with markedly activated coagulation hemostasis, which may justify a prolonged use of low-molecular-weight heparins in the postoperative period, especially in patients with PE.